MUHAMMAD SYUHUDI ISMAIL (1943-1995); TOKOH HADITH PROLIFIK,ENSKLOPEDIK DAN IJTIHAD - Fithriady Ilyas; Ishak bin Hj. Suliaman (Islam Futura, 2017)
This paper aims to investigate the prolific, encyclopedic and ijtihad aspects of an Indonesian hadith figure, Muhammad Syuhudi Ismail.He has brought significant aspects in the development of hadith studies in Indonesia, especially in Islamic Higher Education sectors. This paper is framed by using qualitative approach. In order to collect data, the author compiled both the individual and group work of Syuhudi Ismail; examined other authors work about Syuhudi; and conducted in-depth interviewswith his wife and students. The author used descriptive analysis to analyse the data. The findings show that the productivity of Syuhudi Ismail can be seen from his collections of 59 scientific works dated from the 1970s to 1990s: 8 books, 13 enncyclopedi entries, 38 papers, articles and research reports. From the ijtihad (interpretative) aspect, he is one of proponents of women leadership. Meanwhile, he claimed that plastic surgery for the purpose of enhancing beauty is prohibited. In hadith studies, he introduced the hadith sanad studies by considering the major and minor essence. In understanding the substance of hadith, he preferred the thematic and holistic approach. Finally, this paper concludes by discussing the challenges faced by hadith researchers of Islamic Higher Education sectors today, that is to obtain that aspects, to constantly exploring new methods in hadith studies and producing practical works in the field of hadith studies which are applicable and relevant for wider society.